2019
DOI: 10.31545/aagr/109050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selected biostimulants on the yield and quality of the common onion (Allium cepa L.)

Abstract: Station owned by the University of Warmia and Mazury in Olsztyn. The experiment had a randomized block design with three replications. The first experimental factor was a number of common onion cultivars: 'Whitney Wing F1', 'Spirit F1' and 'Red Baron'. The second experimental factor was the effect of two plant growth biostimulants; Calleaf Aminovital and Maximus Amino Protect, on the yield and quality of the onions. In the control treatment, plots were sprayed with water. The total yield, marketable yield and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…There was no significant effect of Nutrilife and mineral fertilizers on onion sugar content. Similarly, Mikulewicz et al [16] found no changes in the content of total and reducing sugar in three varieties of onion after the use of two biostimulants. On the other hand, Francke et al [6] reported that biostimulants decreased the sugar content of shallot onion in relation to the control.…”
Section: Tablementioning
confidence: 90%
See 2 more Smart Citations
“…There was no significant effect of Nutrilife and mineral fertilizers on onion sugar content. Similarly, Mikulewicz et al [16] found no changes in the content of total and reducing sugar in three varieties of onion after the use of two biostimulants. On the other hand, Francke et al [6] reported that biostimulants decreased the sugar content of shallot onion in relation to the control.…”
Section: Tablementioning
confidence: 90%
“…Whereas, the positive effect of biostimulants on the endive yield was observed by Gajc-Wolska et al [7], and on raspberry yield was shown by Grajkowski and Ochmian [9]. Mikulewicz et al [16] observed differences in the onion yield depending on the type of amino acid biostimulants. The positive effect of biostimulants produced from seaweed extracts on the biometric parameters of onion was also noted by Abbas et al found that biostimulant application had a positive effect on the average weight of bulbs and their yield, regardless of the year of research.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 98%
See 1 more Smart Citation